2006
DOI: 10.1021/op0502194
|View full text |Cite
|
Sign up to set email alerts
|

Practical Synthesis of 2-Amino-5-fluorothiazole Hydrochloride

Abstract: The first synthesis of 2-amino-5-fluorothiazole hydrochloride is reported from 2-aminothiazole. The synthesis proceeds in 35% overall yield, involves no chromatographic purification, and has been employed to prepare multikilogram quantities of the title compound. The key fluorine-introducing step comprises the reaction of dilithiated 2-tert-butoxycarbonylaminothiazole with N-fluorobenzenesulfonimide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 14 publications
2
14
0
Order By: Relevance
“…Starch paper confirmed that the Selectfluor 1 was being consumed by some mechanism, perhaps involving attack by the thiazole nitrogen [17], although no other product could be observed. A similar incomplete conversion upon reaction of 2-acetamidothiazole with Selectfluor 1 was noted by others [15]. Despite our incomplete reaction, we were able to isolate 5-fluorothiazole (8a) in 23% yield following chromatography, with the structure being confirmed by GC-MS, 1 H, 13 C, 19 F NMR, IR, and elemental analysis (vida infra).…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Starch paper confirmed that the Selectfluor 1 was being consumed by some mechanism, perhaps involving attack by the thiazole nitrogen [17], although no other product could be observed. A similar incomplete conversion upon reaction of 2-acetamidothiazole with Selectfluor 1 was noted by others [15]. Despite our incomplete reaction, we were able to isolate 5-fluorothiazole (8a) in 23% yield following chromatography, with the structure being confirmed by GC-MS, 1 H, 13 C, 19 F NMR, IR, and elemental analysis (vida infra).…”
Section: Resultssupporting
confidence: 83%
“…In contrast, preparations employing direct, electrophilic fluorination, as often preferred in analogue preparation, are quite rare. For example, the only report we have been able to find involving thiazoles is the very recent fluorination of the highly activated 2-acetamidothiazole using Selectfluor 1 [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After we had used this procedure, a report appeared confirming our result. 31 These authors, however, found that on a larger scale treatment of Boc-2-aminothiazole with two equivalents of Bu t Li, followed by addition of N -fluorobenzenesulfonimide, then acidolysis with HCl, was a more reliable route to 40 . Coupling of 40 with acetylsalicyloyl chloride followed by standard deprotection gave the 5′-F analogue 14 .…”
Section: Chemistrymentioning
confidence: 99%
“…Such 1,3-thiazoles appear susceptible to metabolism by oxidative ring opening 12. However, one report suggests that fluorination of a 1,3-thiazolyl group might lead to better resistance to metabolism in vivo 13. We hypothesized that the 2-position in 1,3-thiazoles would be an attractive site for facile incorporation of fluorine-18 from [ 18 F]fluoride ion and moreover might deliver a relatively metabolically stable [ 18 F]2-fluoro-1,3-thiazolyl structural motif.…”
mentioning
confidence: 99%